Vitamina A e a homeostase da mucosa intestinal - Samara Rabelo Medeiros (2011)
Vitamin A and its analogs have been in focus of research because of its powerful regulatory effects on cell proliferation and epithelial differentiation in addition to its antioxidant activity (REIFEN et al., 2002). This compound can also differentiate naïve T cells into regulatory T cells (Tregs), when combined with TGF- (MUCIDA et al., 2007). Therefore, our aim in this study is to evaluate the effects of dietary deficiency and supplementation of vitamin A in healthy mice and the activity of this nutrient on intestinal mucosa homeostasis by employing murine models of inflammatory bowel disease. Female C57BL/6 mice, at 4 weeks of age, were fed four different diets, either a normal diet (containing 4000 UI of vitamin A), a vitamin A-free diet, or a Vitamin Asupplemented diet (one containing 10000 UI vitamin A and another containing 50000 UI of this vitamin). After 7 weeks of diet consumption, colitis was induced by oral administration of dextran sodium sulfate (DSS) for 6 days. For each diet there was a control that was not treated with DSS. Cellular profiles of spleen, mesenteric lymph nodes (MLN), Peyers patches (PP) and lamina propria were evaluated, as well as metabolic parameters. In healthy animals that were fed supplemented diets there was an increase in B1 lymphocytes and Tregs in the spleen in addition to an increase in number of Tregs in MLN. Vitamin A-deficient animals showed a reduction in Peyers patches Tregs and an increase in serum IgG and interferon- production when compared with control mice. In mice with colitis, supplementation with vitamin A led to an increase of Tregs in spleen, MLN, PP and lamina propria, whereas vitamin A deficiency caused a decrease of Tregs in spleen. Mice that were supplemented with the higher dose of vitamin A also showed an increase in spleen B1 cells, but this population was reduced in MLN. We observed a higher production of serum immunoglobulin A (IgA) and secretory IgA in mice supplemented with high dose of vitamin A and in vitamin Adeficient mice. Vitamin A supplementation did not cause metabolic disorders in healthy mice nor in mice with colitis. This increase in Tregs supplemented mice as well as their better performance in weight gain and activity during DSS administration suggested an in vivo anti-inflammatory and modulatory role for this compound.